Análise comparativa entre o novo método de dimensionamento nacional de pavimentos: MEDINA e o método do DNER - SILVA, Daniel Cardoso da (2021)
Highways have one of the greatest relevance among the main infrastructure works in the country. In this way, the importance of proper sizing of projects is understood, as keeping them in good condition is a guarantee that drivers will travel comfortably, safely and economically. For this it is necessary that the methods be adapted and that they are able to evaluate the structures in terms of loads and wear and tear of the climate itself, since the current method cannot measure such complexities. This work aims to establish a comparison between the current method of DNIT (DNER) and the new Method of National Dimensioning of Pavements (MeDiNa). The structure studied in this research corresponds to the duplication construction of the BR-316 highway, between kilometers 67.6 and 112.6, in the state of Pará, which will be dimensioned by the two methods. The final structure conceived by the DNER method resulted in a coating of 12.5 cm, base and sub-base of 15 cm, after MeDiNa analysis the structure presented 99.0% of cracked area at the end of the 10 years of design, also indicating a high traffic for the proposed structure. When resized by MeDiNa, the structure underwent changes in the base and sub-base materials, leaving the base thicker than the sub-base, which remained with a constant thickness next to the cladding. The results showed low wheel track sinking and a low percentage of cracked area, however the structure had an increase of 41% in its cost per kilometer.